Fast Determination of Vehicle Suspension Parameters via Continuous Time System Identification*. Issue 11 (2016) - Thaller, Sandra; Reiterer, Florian; Schmied, Roman; Waschl, Harald; Kokal, Helmut; del Re, Luigi
Abstract: Having accurate estimates for the parameter values of different vehicle components is crucial when it comes to the level of virtual testing of vehicle dynamics. Since these values are often not directly available, they need to be obtained from measurements. The most straightforward, but also most expensive way to obtain unknown values is by disassembling the car and by performing tests on the separate vehicle components. A solution that is often much cheaper is to infer estimates of the parameter values from measurements obtained by performing different driving maneuvers with the car. In this paper we show how methods from direct continuous time system identification (CT SysId) can be used to obtain accurate estimates for parameter values of the vehicle suspension system. The dynamic tests consist in exciting the suspension system by driving over one or several small obstacles and by recording the dynamic response of the car. CT Sysld is used to adapt the unknown parameter values of a tentative car model in order to best match the measured data. Evaluation of the approach using a multi-body simulation tool showed that the identified parameter values match well with the ones of the simulated vehicle suspension system.